1993
DOI: 10.1136/adc.68.4.487
|View full text |Cite
|
Sign up to set email alerts
|

Audit of paediatric cardiopulmonary resuscitation.

Abstract: The causes and outcome of cardiopulmonary arrests were studied in a paediatric hospital over a 12 month period. Forty five resuscitation attempts were made involving 41 children and one adult. Twenty eight (68%) of the children were under 1 year of age and 10 (24%) were neonates. This study was undertaken to evaluate the causes of cardiopulmonary arrest in a large paediatric hospital, the response to these by the 'crash team', and the final outcome of attempts at cardiopulmonary resuscitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
4

Year Published

1998
1998
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(23 citation statements)
references
References 11 publications
1
18
0
4
Order By: Relevance
“…Losek et al 15 also investigated out-of-hospital pediatric cardiopulmonary arrest and found few neurologically intact survivors (9 of 114 [8%]). In contrast, Innes and et al 16 showed a 70% success rate, with initial resuscitation of 41 children with inpatient pediatric cardiopulmonary arrest, 10 of whom (24%) were neonates. At 12-month follow-up, 37% were still alive.…”
Section: Pediatric Cardiac and Respiratory Arrest: Success In Resuscimentioning
confidence: 99%
See 1 more Smart Citation
“…Losek et al 15 also investigated out-of-hospital pediatric cardiopulmonary arrest and found few neurologically intact survivors (9 of 114 [8%]). In contrast, Innes and et al 16 showed a 70% success rate, with initial resuscitation of 41 children with inpatient pediatric cardiopulmonary arrest, 10 of whom (24%) were neonates. At 12-month follow-up, 37% were still alive.…”
Section: Pediatric Cardiac and Respiratory Arrest: Success In Resuscimentioning
confidence: 99%
“…An overall cost analysis has not been attempted for pediatric out-of-hospital arrest victims. Health care professionals should be reminded that the Hickey et al study 21 and others [15][16][17] suggest that the best out-comes are obtained for children who respond to basic life support interventions.…”
Section: Barriers To Basic Life Support Training and Implementationmentioning
confidence: 99%
“…A parada respirató-ria primária parece ser causa mais comum do que parada cardíaca primária em crianças [9][10][11][12][13] . Entretanto, a maioria dos relatos de PCR pediátrica contém número insuficiente de pacientes ou utiliza critérios de exclusão que impossibilitam larga generalização dos resultados do estudo para população pediátrica geral.…”
Section: Retrospectivaunclassified
“…Taquicardia ventricular e fibrilação têm sido descritas em 15% ou menos dos pacientes pediá-tricos e adolescentes vítimas de parada cardíaca pré-hospitalar 6,7 , até mesmo quando o ritmo cardíaco é avaliado precocemente 17,18 . A sobrevida após (PCR) pré-hospitalar é, em média, de aproximadamente 3 a 17% na maioria dos estudos, e os sobreviventes, freqüentemente, ficam portadores de seqüelas neurológicas graves 7,[9][10][11]15,[17][18][19][20][21][22][23] . Além disso, a maioria dos relatos de ressuscitação pediátrica é retrospectiva e falha por conter definições de ressuscitação e critérios de inclusão de pacientes inconsistentes.…”
Section: Retrospectivaunclassified
See 1 more Smart Citation